Flying the world's greatest combat aircraft (Amber Books, 2009)
"The Phantom was not a forgiving jet if you didn't listen to it - once you learned to listen to it, the jet was awesome." -Col. William 'Shadow' Schaal, F-4 Phantom II pilot, USAF Flying the World's Greatest Combat Aircraft is a celebration of the experience of flying some of aviation's most spectacular, powerful and dangerous machines. Packed with first-hand interviews with test and combat pilots from the world's air forces, and illustrated with extensively researched and striking imagery, Flying the World's Greatest Aircraft is a thrilling ride alongside the pilots that fly the aircraft every day. Featuring accounts of combat in the F-15 Eagle, training in the B-2 stealth bomber, and ejecting from a Harrier, this book puts the reader directly in the pilot's seat, and will appeal to aviation enthusiasts of any age.